Implementasi Budaya Bersih dalam Mengembangkan Kepedulian terhadap Kebersihan Lingkungan pada Siswa di SD Negeri 07 Kota Bengkulu - Ayu Erdiyanti; Victoria Karjiyati; Neza Agusdianita (Universitas Bengkulu, 2020)
This study aims to determine the effect of ethnomatemics-based Realistic Mathematics Education models on literacy skills in mathematics learning of Grade IV SDN Cluster XIV Bengkulu City. This research is a quantitative research. The method used is quasy experimental design with the type of matching only pretest-posttest control group design. The population in this study was Class IV SDN Cluster XIV Bengkulu City. The sampling technique uses cluster random sampling. The sample in this study was class IV in SDN 52 Bengkulu City as an experimental class and class IV in SDN 24 Bengkulu City as a control class. The research instrument used in the form of a test sheet in the form of a description of 5 questions. Taking the test twice, namely before and after learning takes place in the experimental and control classes. Based on the t-test calculation of students' posttest results, where tcount = 3, 38 and ttable = 2.04. Because tcount> ttable, shows that there are differences in posttest results between the experimental class and the control class. The conclusion in this study there is a significant influence on the use of ethnomatemics-based realistic mathematics education models on literacy skills in mathematics learning of fourth grade SDN cluster XIV Bengkulu city.